NUTRITIONAL AND BIOCHEMICAL CHARACTERISTICS OF LACTIC ACID BACTERIA-CHALLENGED SORGHUM AND ITS FERMENTATION PRODUCT (2012)
Sorghum is one of the major cereals malted for the brewing of beer. The conditions of transport and storage of this cereal predispose it to contamination by microbes thus affecting the quality of the end products. The contamination is usually controlled by treating the sorghum with chemicals, which however alter the chemical constituents of the sorghum. Therefore, the need to seek alternative functional methods of control of microbial contaminants becomes imperative. This study was aimed at investigating lactic acid bacteria as biocontrol agents against microbial pathogens of stored cereals for beer fermentation. Sorghum were obtained from Bodija market and from the Institute of Agricultural Research and Training, Ibadan. Lactic Acid Bacteria (LAB) were isolated from spontaneously-fermenting sorghum and identified using classical techniques. The abilities of the LAB strains to produce antimicrobials and their antagonistic activity against known cereal pathogens were used to select the best three strains for further work. The selected strains were applied singly and in combination at inoculum concentration of 2.3 x 104 cells/mL for five days to challenge sorghum seeds prior to malting and wort production. Sorghum wort was fermented for five days with Saccharomyces carlsbergensis. Physiological and nutritional characteristics of the unchallenged and challenged sorghum, and fermentative characteristics of the wort were determined using the European Brewery Convention methods. Data were analysed using ANOVA. One hundred and twenty seven strains of LAB were isolated and identified as Lactobacillus plantarum (32), Lactobacillus brevis (31), Lactobacillus fermentum (25), Lactobacillus delbrueckii (8), Lactobacillus casei (12) and Lactobacillus acidophilus (19). Lactobacillus plantarum, Lactobacillus fermentum and Lactobacillus casei produced high antimicrobial lactic acid (2.5±0.5g/L, 2.4±0.3g/L and 2.5±0.5g/L respectively) and had high inhibitory activities (17mm, 14mm and 17mm respectively). Lactobacillus brevis produced antimicrobial lactic acid with the highest mean concentration of 2.7±0.5g/L from local sorghum but was not used for further work because the inhibitory activity was low when tested against pathogenic organisms. All the LAB produced bacteriocin with antagonistic effects on all the pathogens tested, and Lactobacillus plantarum had the highest zone of inhibition (17mm) against Bacillus subtilis. All the LAB grew at temperature of 30oC, pH 5.0-5.5, high glucose and peptone concentration (1.5-2.0mg/ml). The malted untreated -sorghum had 13.2 % protein, 3.0 % crude fat, 1.9 % ash, 1.8 % crude fibre, 42.5 mg/g phytate, 36.0 mg/g tannin, 2.0 mg/g protein inhibitor and 16.0 IoBunits diastatic power. Fermentation of the unchallenged wort (pH 6.2) yielded ethanol content of 2.2 %. With LAB treatment, there was a reduction in protein (12.2 %), crude fat (2.1 %) and crude fibre (1.1%); and significant (p<0.05) reduction in antinutrients (phytate 32.7 mg/g, tannin 22.4 mg/g, protease inhibitor 0.0 mg/g and wort pH 4.2). There was also an increase in diastatic power (24.0 IoBunits). The subsequent fermentation produced 4.8 % ethanol. The microbial profiles of the challenged malted sorghum showed a steady decrease in Bacillus, Staphylococcus and Pseudomonas count compared with the unchallenged where they showed steady increase. Lactobacillus starter cultures reduced spoilage pathogens, antinutritional factors of sorghum during malting and improved the end products.